THE IMPACT OF GOVERNMENT ASSIST IN DEVELOPING HATCHERY OF TILAPIA (Oreochromis niloticus) MEMBER IS SEJAHTERA GROUP IN SIDE OF THE POND IN SILAU MALAHA VILLAGE SIANTAR DISTRICT SIMALUNGUN REGENCY NORTH SUMATERA PROVINCE - Sianturi, Betti L; Hendri, Ridar; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 3-14 may 2015. The purpose of this research is to know the development the fish hatchery. Start from the wide of pull the number of production development, the income, and extension of region trade for Sejahtera Group. This research was used survey method. The determination responded was taken with a simple random sampling the population in research was the member of Sejahtera Group who has their own job as hatchery. The number of member is 22 persons. Remembering the characteristic the job of population is relative homogeny so in taking in responden was enough 50% for is hatchery.The result of this research showed that the fish hatchery was done by the member of Sejahtera Group has a good development after accepting the assist from government. The wide of pool before accepting the assist in 2011 was around 909 m² but after get the assist in 2014 the wide of pool becomes 2,672 m², the number of seeds of production which gotten before getting the assist was around 68,091 seeds per year after got the assist from government the number of production increased become 200,454 per year. The income fish hatchery before get the assist 15.403.773,- and after got the assist from government the income is increased to be 47.378.745,- the wide of trade region before got the assist just to region they were Siantar, Balige, Parapat, Porsea, Haranggaol, and Salbe.Key Word : The Impact Of Government Assist, The Business Development, And Fish Hatchery